Fasting Blood Glucose Test in Nepal - Time for a Harmonized Definition - Pant, Vivek; Gautam, Keyoor; Pradhan, Santosh (Journal of Nepal Health Research Council, 2019)
There are various views in defining protocols for fasting blood glucose test currently being used by healthcare providers in Nepal. A number of modifiable factors can influence the result of an estimation of fasting blood glucose in a clinical laboratory. Variations in the results of fasting blood glucose tests are usually controlled by minimizing the discrepancies in the pretesting variables, one of which is the inconsistency in what represents fasting. In order to minimize the complications of erroneous reporting of fasting blood sugar tests, it is crucial to define the protocols for the test and adopt them in unison by all clinical laboratories of Nepal. Keywords: Clinical laboratory; fasting blood glucose; pretesting variables.